Social Network Analysis and Digital Learning Environments: A Framework for Research and Practice Using the SAPO CAMPUS Platform - Pedro, Luís (2018)
The main purpose of this study is to explore the research underlying the development of Social Network Analysis (SNA) features in the SAPO Campus platform, aiming to provide a set of analysis tools that can help managers, teachers and researchers to understand and react timely on the evolution of their communities. The paper presents the SAPO Campus digital platform, and the basic principles of SNA are described. To justify the rationale underlying the selection of SNA's features, a use case is described. The case is about using those features to analyse a dynamic social structure:) space in SAPO Campus. Tools such as Gephi were used to collect and format data into a graph network. The collected data refers to the period 2012-2015, with 1,001 registered users in the platform. SNA features were applied to analyze the network in terms of cohesion, degree, centrality, and group structure. The findings indicate that the analyzed network corresponds to the organization in scientific areas in DeCA, and the results found echo the perception that the authors have of the platform use. Also, results show the importance of some teachers in the promotion and dynamics of the network. These findings help to justify the use of SNA to analyze networks of this nature. However, the authors acknowledge that a more detailed interpretation of the results depends on deep knowledge of the studied network connections, suggesting that the implementation of SNA must be triangulated with complementary application of qualitative techniques. This study provides valuable insights to the development of the SNA export tool for the SAPO Campus platform under the GAMILearning project, and to a more general application of the SNA techniques as well.